Implementasi model problem-based learning (PBL) sebagai upaya meningkatkan kemampuan berpikir kritis peserta didik sekolah dasar: Literature review - Aisyah, Fenty Nur; Gumala, Yosi (Papanda Journal of Mathematics and Science Research, 2025)
An ineffective or inefficient teaching model can be a contributing factor to the suboptimal development of students logical and deep thinking skills. To enhance students critical thinking abilities, innovation is required to successfully improve the quality of learning. The Problem Based Learning approach can be utilized as an option or alternative solution to improve the quality of education. This literature review aims to identify and analyze 30 articles related to the application of the PBL model at the elementary school level, specifically focusing on its use as a strategy to enhance students critical reasoning skills. The study employs a literature review approach, which involves stages of identifying relevant references on the topic of interest, analyzing them, selecting the most pertinent sources, and thoroughly examining each reference used. Based on the reviewed literature, findings indicate that the PBL approach has a positive impact on learning activities and successfully enhances the critical reasoning skills of elementary school students, a crucial competency to master in order to face the challenges of the 21st century. The findings of this literature review are expected to provide valuable insights and serve as a reference for future researchers and educators in managing classroom learning.